Refocused psychotherapy as the first line intervention in behavioral health - Cummings, Nicholas A. (Routledge, 2013)
"Written by father-daughter psychologists Nick and Janet Cummings, this text provides proven patient-responsive interventions by practitioners who together have nearly a century of hands-on practice and innovation between them. Refocused Psychotherapy responds directly to the recent decline of psychotherapeutic practice, where medications have replaced psychosocial services as the dominant treatment modality, just as its precursor, Focused Psychotherapy, was written in the 1990s to aid psychotherapists in response to rapidly growing managed care. The case histories, treatment modalities, and standards found in this book center around the Biodyne Model, an evidence-based system with roots in Kaiser Permanente. It has been field-tested for over four decades with a national patient cohort of over 25 million and is the only behavioral healthcare system subjected to such extensive ongoing evidence testing. The authors demonstrate how the Biodyne Model advocates efficacy, effectiveness, and efficiency--the standards psychotherapeutic intervention is held up to. They also teach readers how to treat their patients differently and to diagnose in accordance with effectiveness through their onion/garlic conceptualization. Readers will develop the skills necessary to demonstrate therapeutic results as well as cost-effectiveness through this innovative and revealing book"--